A RESEARCH ON EVALUATION OF THE PROBLEMS OF WOMEN WORKING IN TOURISM SECTOR - MAHMUT BARAKAZI (Fırat University, 2019)
With the global growth of the tourism sector, the economic effects have increased steadily. One of the first of these influences is the employment capacity that created it. The fact that modern people have differences in their working lives after industrialization has led women to intensively enter business life. Women's employment has provided employment in many areas, including in different business sectors. As a result, women's early inequality in work life was tried to be solved and tried to benefit more from human qualities. The tourism sector has a structure that requires heavy employment due to its location in the service field. Women's employment in the sector is used in coastal hotels, travel agencies, transportation companies and stakeholder sectors. However, in regions where education is not very high, employment of women in the tourism sector is very difficult. In these regions, it is thought that there are many reasons such as the tendency of traditional viewpoints to change, oppressive and hard-to-use tendencies, and contempt of women's working qualities. The purpose of this study is to determine the thoughts of women about gender discrimination by putting obstacles in front of women employment in tourism enterprises in Şanlıurfa which has very rich tourism capacity in terms of cultural and belief dimension. The isolation of women's qualities, There are some suggestions and ideas to remove the gender discrimination that women working in the tourism sector are exposed to in the workplace. one of the most important elements of our culture, from the tourism sector suggests that both social development and economic development will come to a halt.